Introduction: The legacy of Bhekizizwe Peterson for Psychology in Society - Bradbury, Jill; Kiguwa, Peace (PINS-Psychology in Society, 2024)
This special issue of PINS commemorates and celebrates the work and thought of the late renowned Professor of African literature and award-winning film-maker, Bhekizizwe Peterson. From different angles, the authors in this volume place psychology in dialogue with Peterson’s work, continuing a transdisciplinary conversation in which he was a consistently generous and enlivening interlocutor. Contemporary imperatives to decolonise intellectual traditions and reconceptualise personhood and psychic life in historical, social and political terms, are articulated in a societal context (South Africa and beyond, across the continent and the globe) that is repeatedly described as ‘in crisis’. In the here-and-now, the explicit agenda of PINS to explore psychology in society, entails theorising human life in pervasively dehumanising conditions of inequality, intergenerational trauma, and the precarity of planetary life. Peterson has much to say to these critical questions, and this special issue provides a unique opportunity for the readers of PINS to engage with his remarkable oeuvre of scholarly, artistic and activist work across the fields and modalities of lliterature, film, and literary and social criticism, opening up invigorating lines for re-thinking the disciplinary praxis of psychology.